THE USE OF GENOGRAM TECHNOLOGY IN THE WORK OF A SOCIAL PEDAGOGUE AS A TOOL FOR REVEALING THE SOCIO-PEDAGOGICAL DYNAMICS OF THE FAMILY (EDUCATION IN THE 21ST CENTURY, 2025)
Modern social pedagogy emphasizes the in-depth study of family structure and interpersonal relationships to fully understand the processes of a child’s socialization. In this context, the genogram, as a methodological tool, makes it possible to visually represent the system of family generations, their connections, roles, and internal dynamics. The process of creating a genogram is not only an informational map but also a creative form of expression that encourages family members’ involvement, reveals latent social ties, and fosters the awareness of intergenerational experience. For social pedagogues, this technology is particularly valuable when working with at-risk families, implementing preventive programs, and developing individuale support strategies. The study aims to substantiate the use of genogram technology in social pedagogy as a tool for identifying family socio-pedagogical dynamics.
Keywords: genogram; social pedagogue; family; technology; art therapy; socialization; process; informational map; generation; strategy